UPAYA PENINGKATAN PEMAHAMAN NILAI PANCASILA TERHADAP SISWA MELALUI KEGIATAN PENYULUHAN - Wendy Anugrah Octavian (Bhineka Tunggal Ika: Kajian Teori dan Praktik Pendidikan PKn, 2019)
abstract: This counseling activity is part of community service that aims to increase student understanding of the values of Pancasila. The final goal of efforts to understand the values of Pancasila is so that students can apply these values in their daily activities. The participants of the counseling were students at SDN 22 Tanjung Batu, Ogan Ilir Regency. The inculcation of Pancasila values to students is intended so that these values can be possessed by students from an early age, bearing in mind that many external influences also adversely affect the lives of children including those in elementary school. Community service activities are carried out using participatory action methods in the form of lectures and discussions. The implementation of this method is used to convey material, one of which is the lecture method after that is used for discussion and question and answer. Changes in the level of student understanding of Pancasila values are measured by giving students a pretest at the beginning of the activity and a posttest at the end of the activity. Based on the results of the comparison of the pretest and posttest scores it can be concluded that there is an increase in students' understanding of the values of Pancasila. Keywords: Planting, Pancasila values, Counseling